Impacts of China's Emissions Trading Scheme on the National and Hong Kong Economies: A Dynamic Computable General Equilibrium Analysis - Wang, Yue; Winchester, Niven; Webster, Christopher J.; Nam, Kyung-Min (Frontiers in Environmental Science, 2020)
In this study, we estimate the economic impacts of China’s official carbon-mitigation targets, in connection with Hong Kong’s potential participation in a proposed national emissions trading scheme. We find that moderate intensity-reduction targets emulating China’s pledged Paris Agreement commitment would incur much larger policy-compliance costs in Hong Kong (0.1% - 2.5% of baseline gross domestic product) than in Mainland China (0.1% - 0.7%) in each of the modelled years 2021 to 2030 when each economy operates its own independent carbon market. By comparison, an integrated carbon market enables Hong Kong to achieve the same reduction goal at up to 78% lower costs compared to an independent market, and this is achieved without significantly affecting the Mainland’s economy. These savings in compliance costs for Hong Kong are greater when pre-integration local carbon prices in both economies are subject to a larger gap. Effectively, the cheaper pre-integration carbon prices in the Mainland indirectly subsidize the Hong Kong economy in the initial years of the integration scenario, buffering the policy shock. In sum, an integrated carbon market in China would improve overall efficiency at the national level, but the benefits are biased toward Hong Kong. This finding suggests that it is in the city’s interest to play a more active role in cross-border collaboration on climate mitigation and emissions trading.